Biochar como suporte de fotocatalisadores a base de ferro para degradação de corantes via processo foto-fenton heterogêneo - Leichtweis, Jandira (2023)
Rhodamine B, ponceau, methylene blue and tartrazine dyes are among the most commonly used dyes in the textile and food industries. One of the main techniques studied to remove these pollutants from wastewater are the Advanced Oxidative Processes, with emphasis on the heterogeneous photo-Fenton process, which consists of the combination of an iron-based photocatalyst, an oxidizing agent and UV-Vis radiation. Due to recombination between electron/hole pairs, particle agglomeration and higher band gap value of pure photocatalysts, an advantage is to support them in another material and to circumvent this problem. Thus, in the present study, the ferrites CuFe2O4, CoFe2O4, ZnFe2O4 and MgFe2O4 were synthesized and supported in biochar from malt bagasse, chitin and coffee grounds, respectively. The composites were characterized by XRD, FT-IR, SEM-EDS and UV-Vis. The results of the characterizations showed that the synthesis was effective, as well as the support. The band gap energies of the supported photocatalysts were lower than those of the pure ferrites. Pure ferrites CuFe2O4, CoFe2O4, ZnFe2O4 and MgFe2O4 obtained efficiencies of 39, 78, 38 and 52% for color removal of rhodamine B, ponceau, methylene blue and tartrazine dyes, respectively. On the other hand, the composites obtained better efficiencies: 88% for Rhodamine B (CFO1BM3) and 100% for ponceau, methylene blue and tartrazine (CFO1BQ1, ZFO1BC1 and MFO1BC1, respectively) in the same period of time. When the new supported photocatalysts were applied to the photo-Fenton process, there was greater degradation using the materials supported on biochar compared to pure ferrites. Proving that the support helps to reduce the recombination of electron/hole pairs, it prevents the agglomeration of ferrites, which tend to agglomerate due to their magnetic properties, in addition to having a lower band gap, being more efficient in the visible light region. These results were obtained using the best experimental conditions found: pH 3, 100 µL of H2O2 and 1 g L-1 of photocatalyst. The recycling of composites indicated that they can be used in eight cycles without major efficiency losses (less than 20%). In the proposed mechanism, it was verified that the radicals •OH and •O2 -were the predominant reactive species involved in the removal of dyes. LC-MS/MS analyzes showed that rhodamine B and tartrazine dyes were reduced to low m/z intermediates and toxicity tests using Danio rerio fish indicated that ponceau and methylene blue dyes showed less toxicity after treatment. The results showed that the new composites formed (CuFe2O4/Biochar, CoFe2O4/Biochar, ZnFe2O4/Biochar and MgFe2O4/Biochar) are promising photocatalysts for the removal of organic pollutants present in water.